Innovation management in agriculture through Artificial Intelligence - Singh, Vikram; Varshney, Himanshu; Datt, Shiv (Indian Farming, 2019)
Application of information technology in agriculture changes the life of the farmers from the long queues before government offices to click on their cell phones. Now gone are the days when farmers were used stand in queue to get a copy of their revenue records, payment of electricity bills, subsidy on fertilizers/equipment/sees, farm loan applications, society memberships, farm inputs at cooperative society etc. All these services are now available on hand, where they can get the information in advance. As our world becomes increasingly digital smart algorithms, bots and Artificial Intelligence tools will no longer be the exception for organizations, but the norm.